An educational intervention on HPV knowledge and comfortability discussing vaccination among oral health care professionals of the American Indian and Alaskan Native population - Moaiad H. Salous; Marie Abele Bind; Louis Granger; Lisa Bennett Johnson; Kelly Welch; Alessandro Villa (Taylor & Francis Group, 2020)
This study aimed to evaluate the effectiveness of an educational intervention at improving Oral Health Professionals (OHP's) knowledge of HPV and comfortability to discuss vaccination with their American Indian and Alaskan Native patients. OHP's attended an educational lecture covering HPV vaccination. Participants completed four validated questionnaires that encompassed a sociodemographic survey, a pre-lecture questionnaire (pre-Q), a post-lecture questionnaire (post-Q), and a follow-up questionnaire (follow-Q). The McNemar test was used to assess the significance of marginal probabilities in the responses between the pre-Q and post-Q and the Chi-square test to assess responses between the post-Q and follow-Q. A total of 122 OHP's completed the sociodemographic survey, pre-Q, and post-Q. Among these, 29 OHP's completed the eight-week follow-Q. The majority of all the participants were White/Caucasian (41%), 31 to 60 years of age (72%), females (64%), and held a graduate/professional degree (52%). Analysis of the pre-Q responses showed that only 6.8% of OHP's discuss the connection between HPV and oropharyngeal cancer with patients and a lack of information on the topic was the major barrier reported. After the educational intervention (post-Q), 86.5% of OHP's reported they were more likely to recommend the HPV vaccine and 69.8% felt more comfortable administering it. Comparison between the pre-Q and the post-Q showed a significant improvement in overall HPV knowledge. Similarly, a comparison between the post-Q and the follow-Q showed retained knowledge overtime. Our study suggests that the educational intervention was effective at improving OHP's knowledge of HPV and enhancing their comfortability and preparedness to discuss the vaccination with their patients.